ANALISIS SEKTOR UNGGULAN PEREKONOMIAN KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - tabrani, andi (Badan Pengkajian dan Penerapan Teknologi, 2008)
Identification process for Basis Sector(s) in a region must be conducted in order to develop the economic development planning. The identification could be conducted through the Location Quotient (LQ) analysis. This paper discuss about LQ analysis toward Mandailing Natal Regency. This regency is part of North Sumatera Province in Indonesia. According to the LQ analysis, the economy of Mandailing Natal Regency depend on the primary sector i.e. Agriculture sector and Mining & Quarrying sector. It means that those sectors are the source of income for Mandailing Natal Regency.